The mediating effect of customer satisfaction on corporate social responsibility dimensions and customer loyalty in Maybank, Shah Alam / Nur Huda Husna Mohd Idris - Mohd Idris, Nur Huda Husna (2018)
The purpose of this study is to examine the mediating effect of customer satisfaction on Corporate Social Responsibilities (CSR) dimension and customer loyalty in banking sector. The research was conducted on 287 of bank customers in Shah Alam, Selangor. The corporate social responsibilities was not new issue in Malaysia, however there were little study had been done on corporate social responsibilities in banking sector using Carroll model CSR dimensions. Most the previous study done on CSR using the CSR framework as provided in Bursa Malaysia Listing Requirement (BMLR). Hence, the banking sector was chosen as a place for research method due to huge demographic profile of respondent especially in Selangor. The findings showed a positive relationship between the customer satisfaction and corporate social responsibilities dimension which consist of philanthropic CSR, economic CSR, legal CSR and ethical CSR. Moreover, the relationship between customer satisfaction and customer loyalty indicates that the when customers satisfied with the services and products of the industry (banking sector in this study), the customers will remain loyal to the organization. This study believed to enhance the understanding of knowledge of the organization toward customer satisfaction on corporate social responsibilities dimension on customer loyalty in Malayan Banking Berhad (Maybank) Shah Alam, Selangor, Malaysia context.